Contribution of forest species to the floristic composition of a forested savanna in southeastern Brazil - Pinheiro,Marcelo Henrique Ongaro (2006)
Based on studies of floristic lists the contribution of forest tree and shrub species in a forested savanna area in the city of Bauru, State of São Paulo, and in 14 different places sheltering cerrado sensu stricto and cerradão in Brazil is defined as the evidence of forest species causing a change of cerrado heterogeneity. The percentages of occurrence of forest species in the locations analyzed varied from zero to 4.5%. The proximity of different forest matrices, the occurrence of fires and the inclusion criteria used were some of the factors that may have influenced such variation.